Measurement of molten chocolate friction under simulated tongue-palate kinematics: effect of cocoa solids content and aeration - Samaras,G; Bikos,D; Vieira,J; Hartmann,C; Charalambides,M; Hardalupas,Y; Masen,M; Cann,P (Current Research in Food Science, 2020)
The perception of some food attributes is related to mechanical stimulation and friction experienced in the tongue-palate contact during mastication. This paper reports a new bench test to measure friction in the simulated tongue-palate contact. The test consists of a flat PDMS disk, representing the tongue loaded and reciprocating against a stationary lower glass surface representing the palate. The test was applied to molten chocolate samples with and without artificial saliva. Friction was measured over the first few rubbing cycles, simulating mechanical degradation of chocolate in the tongue-palate region. The effects of chocolate composition (cocoa solids content ranging between 28 wt% and 85 wt%) and structure (micro-aeration/non-aeration 0–15 vol%) were studied. The bench test clearly differentiates between the various chocolate samples. The coefficient of friction increases with cocoa solids percentage and decreases with increasing micro-aeration level. The presence of artificial saliva in the contact reduced the friction for all chocolate samples, however the relative ranking remained the same.